PENGHITUNGAN PREMI ASURANSI LONG TERM CARE UNTUK MODEL MULTI STATUS - Gumauti, Chrysmandini Pulung; Wilandari, Yuciana; Rahmawati, Rita (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Health insurance is insurance that provides health benefit in the form of a cash compensation for the cost of treatment and care. One of the health insurance’s products is Long Term Care (LTC) insurance. LTC insurance guarantees nursing and medical expense, preferred for elderly people in the future. Proper calculation the cost of premiums is needed to maintain the reserve fund appropriate for insurance company to fulfill the policy agreement. In this final project will be discussed about calculation of premiums for LTC insurance products Annuity as A Rider Benefit as a multi-state models (three states), which is based on Markov transition probability matrix. Data used is the data prevalence rate of heart disease in the United Kingdom in 2014. By calculating premiums of multi-state models, insurance products are expected to be able to guarantee health care expense according insured’s needs. Result of this premiums calculation is the older someone takes insurance, greater the annual net premium to be paid. Keywords: health insurance, Long Term Care insurance, multiple state models, Annuity as A Rider Benefit product, Markov transition.